2022
DOI: 10.1186/s40538-022-00326-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactiplantibacillus plantarum inoculation on the quality and bacterial community of whole-crop corn silage at different harvest stages

Abstract: Background Silage is achieved by anaerobic fermentation of lactic acid bacteria. However, harvest stage and Lactiplantibacillus plantarum (L. plantarum) content affect the changes of microbial community in silage, which play an important role in silage quality and mycotoxin levels. The current study evaluated the effects exerted by the application of L. plantarum on fermentation, mycotoxins and bacterial community of whole-crop corn silage at different harvest stages. The fresh whole plant corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
3
6
0
Order By: Relevance
“…Proteolysis is a critical issue in silage fermentation, with high NH 3 -N content indicating extensive protein degradation ( Tao et al, 2020 ). This study found that after 56 days of ensiling, the NH 3 -N concentration in the additive-treated silages was lower compared to CK silages, aligning with Dong et al (2022) , who reported LAB’s role in improving silage fermentation quality and reducing protein hydrolysis. The decrease in NH 3 -N content in additive-treated silage may result from the inhibition of Clostridium and other proteolytic bacteria by the low pH environment, thereby preserving the CP content ( Dong et al, 2022 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Proteolysis is a critical issue in silage fermentation, with high NH 3 -N content indicating extensive protein degradation ( Tao et al, 2020 ). This study found that after 56 days of ensiling, the NH 3 -N concentration in the additive-treated silages was lower compared to CK silages, aligning with Dong et al (2022) , who reported LAB’s role in improving silage fermentation quality and reducing protein hydrolysis. The decrease in NH 3 -N content in additive-treated silage may result from the inhibition of Clostridium and other proteolytic bacteria by the low pH environment, thereby preserving the CP content ( Dong et al, 2022 ).…”
Section: Discussionsupporting
confidence: 85%
“…Consequently, WSC content is lower in the additive group than in the control group due to significant WSC consumption by LAB during fermentation. In this study, the CP contents of LP, LB, and LPB showed an increase compared to the CK group, correlating with Dong et al (2022) , who found that lower pH inhibits plant protease and microbial activities, retaining CP content.…”
Section: Discussionsupporting
confidence: 76%
“…In the high DM silage such as straw forage and native grass, the water activity of LAB is insufficient, so the silage fermentation is reduced due to insufficient metabolic water required for the growth of LAB ( Borreani et al., 2018 ). Four LAB strains produced a large amount of LA and a certain amount of AA to decrease the pH and inhibit the activity of proteases in plants and microbes and reduce proteolysis using a series of substrates ( Dong et al., 2022 ; Lu et al., 2022 ). Similarly, Si et al.…”
Section: Discussionmentioning
confidence: 99%
“…Applying LAB inoculant (T3) on maize silage during ensiling favoured the dominancy of phylum Bacteroidetes followed by phyla Firmicutes and Proteobacteria. On the contrary, Jaipolsaen et al [48] and Dong et al [49] reported Firmicutes bacteria as the dominant phylum on maize silage treated with LAB inoculant during ensiling. However, other studies reported Proteobacteria as the dominant phylum on silage produced from different forages while treated with LAB inoculant during ensiling [20,27,41].…”
Section: Silage Microbial Composition As Influenced By Additivesmentioning
confidence: 96%